EFEKTIVITAS PENGGUNAAN FITUR QR CODE DALAM MENGHIMPUN DANA ZIS (STUDI KASUS BAZNAS PALOPO) - Attas, Luthfiah Mahira; Darwis, Muhammad; Ramadhani, Muhammad Yassir Akbar (IAIN BONE, 2024)
AbstractThis research aims to determine the effectiveness of using the QR code feature in collecting zakat infaq and alms (ZIS) funds at BAZNAS Palopo City. This research is empirical research with a statutory approach and uses qualitative data analysis. Researchers obtained primary data by conducting interviews with the deputy head of zakat collection at BAZNAS Palopo City, employees of Bank SULSELBAR and Bank Syariah Indonesia. Data collection techniques were carried out by means of observation, interviews and documentation in order to find data related to the problem being studied. After obtaining the data in the field the researcher also carried out data analysis using other library data sources. After all the data was collected, the researcher then compiled the existing data so that conclusions could be drawn to answer the problems in this research.The results of this research show that: 1. BAZNAS Palopo City has upgraded digital payments in the zakat, infaq and alms payment system via bank transfer and QR Payment which has been attached to the infaq boxes that have been distributed. 2. The effectiveness of implementing the digitalization system with QRIS barcode scanning in collecting ZIS funds at BAZNAS Palopo City tends to still be less than optimal. 3. Collecting ZIS via QR Payment by scanning QRIS barcodes is still less effective because public literacy regarding digitalization, especially the use of QR Codes, is still lacking due to insufficient socialization factors. Apart from that, the awareness of the people of Palopo City regarding mandatory zakat tends to be low so that the collection of ZIS funds at BAZNAS Palopo City is less than optimal.AbstrakPenelitian ini bertujuan untuk mengetahui efektivitas penggunaan fitur qr code dalam menghimpun dana zakat infaq dan sedekah (ZIS) di BAZNAS Kota Palopo. Penelitian ini merupakan penelitian empiris dengan pendekatan perundang-undangan dan menggunakan analisis data kualitatif. Peneliti memperoleh data primer dengan melakukan wawancara bersama wakil ketua bidang pengumpulan zakat di BAZNAS Kota Palopo, karyawan Bank SULSELBAR dan Bank Syariah Indonesia. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, dan dokumentasi guna menemukan data yang berkaitan dengan masalah yang diteliti, setelah memperoleh data di lapangan peneliti juga melakukan analisis data dengan sumber data pustaka yang lain. Setelah semua data terkumpul, selanjutnya peneliti menyusun data yang ada sehingga dapat ditarik kesimpulan untuk menjawab permasalahan pada penelitian ini.Hasil penelitian ini menunjukkan bahwa: 1. BAZNAS Kota Palopo telah melakukan upgrading digital payment dalam sistem pembayaran zakat, infaq dan sedekah via transfer bank dan QR Payment yang telah ditempelkan di kotak infaq yang telah tersebar. 2. Efektivitas dari penerapan sistem digitalisasi dengan scan barcode QRIS dalam penghimpunan dana ZIS di BAZNAS Kota Palopo cenderung masih kurang maksimal. 3. Penghimpunan ZIS melalui QR Payment dengan melakukan scan barcode QRIS masih kurang efektif dikarenakan literasi masyarakat terhadap digitalisasi khususnya penggunaan QR Code masih kurang yang disebabkan faktor sosialisasi yang kurang. Selain itu, kesadaran masyarakat Kota Palopo terkait wajib zakat cenderung masih rendah sehingga penghimpunan dana ZIS di BAZNAS Kota Palopo kurang optimal.